Prevention of Incisional Hernias by Prophylactic Mesh-augmented Reinforcement of Midline Laparotomies for Abdominal Aortic Aneurysm Treatment: Five-year Follow-up of a Randomized Controlled Trial. Issue 4 (28th October 2022) - Dewulf, Maxime; Muysoms, Filip; Vierendeels, Tijl; Huyghe, Marc; Miserez, Marc; Ruppert, Martin; Tollens, Tim; van Bergen, Liesbeth; Berrevoet, Frederik; Detry, Olivier
Abstract : Introduction: The incidence of incisional hernias (IHs) after open repair of an abdominal aortic aneurysm (AAA) is high. Several randomized controlled trials have reported favorable results with the use of prophylactic mesh to prevent IHs, without increasing complications. In this analysis, we report on the results of the 60-month follow-up of the PRIMAAT trial. Methods: In a prospective, multicenter, open-label, randomized design, patients were randomized between prophylactic retrorectus mesh reinforcement (mesh group), and primary closure of their midline laparotomy after open AAA repair (no-mesh group). This article reports on the results of clinical follow-up after 60 months. If performed, ultrasonography or computed tomography were used for the diagnosis of IHs. Results: Of the 120 randomized patients, 114 were included in the intention-to-treat analysis. Thirty-three patients in the no-mesh group (33/58—56.9%) and 34 patients in the mesh group (34/56—60.7%) were evaluated after 5 years. In each treatment arm, 10 patients died between the 24-month and 60-month follow-up. The cumulative incidence of IHs in the no-mesh group was 32.9% after 24 months and 49.2% after 60 months. No IHs were diagnosed in the mesh group. In the no-mesh group, 21.7% (5/23) underwent reoperation within 5 years due to an IH. Conclusions: Prophylactic retrorectus mesh reinforcement after midline laparotomy for the treatment of AAAs safely and effectively decreases the rate of IHs. The cumulative incidence of IHs after open AAA repair, when no mesh is used, continues to increase during the first 5 years after surgery, which leads to a substantial rate of hernia repairs.